2022
DOI: 10.1111/ane.13604
|View full text |Cite
|
Sign up to set email alerts
|

Clinimetric study and review of the Reaction Level Scale

Abstract: Numerous clinical tools have been used for the assessment of consciousness, with the Glasgow Coma Scale (GCS) 1,2 remaining the gold standard. [3][4][5] The Reaction Level Scale 85 (RLS) 6 was developed to surpass some drawbacks of the GCS, namely low interrater reliability, weak delineation of coma, and insufficient patients' coverage (the extent to which the scale cannot be fully implemented, such as the verbal element in intubated patients). 7 The scale includes 8 single-line steps, each representing a leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…AUC values of approximately 0.900 were expected, and the level of difference between them was set at 5%. It was found that 18 subjects for AUC calculations and 84 subjects for comparisons would reach a power of 80% and a 5% level of significance, which were considered appropriate for the purposes of the current study [ 25 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…AUC values of approximately 0.900 were expected, and the level of difference between them was set at 5%. It was found that 18 subjects for AUC calculations and 84 subjects for comparisons would reach a power of 80% and a 5% level of significance, which were considered appropriate for the purposes of the current study [ 25 , 38 ].…”
Section: Methodsmentioning
confidence: 99%